Analysis Effect of Nutrition Intake on Lung Function of Active Smoker and Non Smoker (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Smoking is major cause of respiratory disorders and the data report in 2012 shows in Indonesia there are 384.058 cases of disesase caused by cigarettes. Nicotine and other substance in cigarette smokes are known that will affect nutritional intake and lung function of active smokers. This study observed healthy adult males aged 18-40 who were divided into two groups of active smokers with minimal 2 years exposure to filter type cigarettes and nonsmoker in 2018. Purpose of this study are to analyze the influence of smoking on nutrition intake and lung function and compared the results with nonsmoker groups. Data from 63 respondents in each group showed significant differences in nutrition intake and lung function (%FVC dan %FEV1) (p=0,001) in both groups. Results of this study showed an average caloric intake of 1787,37 calories and decreased the value of %FVC and %FEV1 respectively 90,48% and 96,83% of respondents in the active smokers group. Results of correlation test showed there is a significant relationship between nutritional intake on lung function.